Hindu Legal Philosophy in Ngelinggihang Dewa Hyang Tradition: A Case Study in Jero Kuta Customary Village - Wisnawa, Dewa Ketut (Udayana Journal of Law and Culture, 2021)
This article discusses Ngelinggihang Dewa Hyang ceremony in Gianyar Regency which is different from the traditions in other regions in Bali.  This tradition originates from Hindu law but is implemented differently by each customary village.  This study aims to assess the position of Hindu law in Indonesian legislation, discuss Hindu law as the basis for implementing Ngelinggihang Dewa Hyang ceremony, identify the autonomy of customary village in Ngelinggihang Dewa Hyang process, and reveal the public perceptions of this ceremony in Jero Kuta Customary Village, Batubulan Village, Sukawati District, Gianyar Regency. This paper is a socio-religious research that is combined with a legal research. The research suggested that Hindu law does not have an explicit position in national law, but is used as the guideline for Balinese customary law. Sources of Hindu law used in this ceremony are Lontar Purwa Bhumi Kamulan and Manawa Dharmasastr a that have been derivated into customary law. The autonomy of the customary village in the process of Ngelinggihang Dewa Hyang can be seen from the dresta (customary law) adopted by the villagers of Jero Kuta Customary Village who carry out this procession on a different day from other rituals. The public perception of this ceremony can be seen from the interaction in family and community scope. It has been revealed that the society does not fully understand the meaning of this religious procession d ue to the following factors; differences in community understanding of the existence of the Ngelinggihang Dewa Hyang ceremony; ignorance of the community, education Level, and the development of globalization in people's life .